EXPRESSION OF FoxP3 TRANSCRIPTION FACTOR IN BRONCHIAL ASTHMA - A. V. Eremeeva (SPb RAACI, 2016)
Forty-two patients with allergic bronchial asthma (ABA) forty persons with non-allergic bronchial asthma (NABA), and 47 healthy controls were involved into the study. Expression of FoxP3 mRNA was analyzed by RT-PCR. In patients with bronchial asthma (ABA and NABA) we have revealed a significant decrease in FoxP3 mRNA expression levels, in comparison with control group. The patients with severe BA exhibited lowest levels of the FoxP3 mRNA expression as compared with other groups.We revealed a decreased FoxP3 mRNA expression in mononuclear cells from peripheral blood, and an increased IL-17 level in blood serum of patients with bronchial asthma. These results may be considered a manifestation of serious inflammatory process. Probably, the data may reflect a disregulated expression of FoxP3 transcription factor. Therefore, we may assume a key role of FoxP3 for regulation of inflammatory activity in bronchial asthma.